Interlaboratory validation of an improved method for detection of Cyclospora cayetanensis in produce using a real-time PCR assay. (February 2018) - Murphy, Helen R.; Cinar, Hediye Nese; Gopinath, Gopal; Noe, Kathy E.; Chatman, Lacresha D.; Miranda, Nancy E.; Wetherington, June H.; Neal-McKinney, Jason; Pires, Gabrielle S.; Sachs, Elizabeth; Stanya, Kristopher J.; Johnson, Cynthia L.; et al.
Abstract: A collaborative validation study was performed to evaluate the performance of a new U.S. Food and Drug Administration method developed for detection of the protozoan parasite, Cyclospora cayetanensis, on cilantro and raspberries. The method includes a sample preparation step in which oocysts are recovered from produce using an enhanced produce washing solution containing 0.1% Alconox and a commercially available method to disrupt the C. cayetanensis oocysts and extract DNA. A real-time PCR assay targeting the C. cayetanensis 18S rDNA gene with an internal amplification control to monitor PCR inhibition provides species-specific identification. Five laboratories blindly analyzed a total of 319 samples consisting of 25 g of cilantro or 50 g of raspberries which were either uninoculated or artificially contaminated with C. cayetanensis oocysts. Detection rates for cilantro inoculated with 200, 10, and 5 oocysts, were 100%, 80%, and 31%, respectively. For raspberries, the detection rates for samples inoculated with 200, 10, and 5 oocysts were 100%, 90% and 50%, respectively. All uninoculated samples, DNA blank extracts, and no-template PCR controls were negative. Reproducibility between laboratories and analysts was high and the method was shown to be an effective analytical tool for detection of C. cayetanensis in produce. Highlights: A new detection method was developed for Cyclospora cayetanensis in produce. The method was validated using cilantro and raspberries in a collaborative study. Molecular detection is performed by real-time TaqMan PCR. An internal amplification control monitors for real-time PCR inhibition. As few as 5 C. cayetanensis oocysts were detected reproducibly on seeded samples.